Hubungan antara Kepuasan Kerja dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior pada Karyawan - Rani Tunbaity Gultom; Noor Erdianza; Rion Nofrianda (Psyche 165 Journal, 2020)
The purpose of this study was to examine the relationship between work satisfaction, organization commitment to organizational citizenship behavior employees. A measuring tool used in this study is the scale of organizational citizenship behavior, work satisfaction, and organization commitment. The sampling technique used was random sampling. The sample population of this study is the employee of company X in Yogyakarta who has a position at low manager. There are 43 employees respondent. This study uses data processing test using SPSS version 21.0 for windows. We use regressions test analysis and the result are a) Ha received, r=0,616 with a value of p = 0.000, p<0.05 means that job satisfaction and OCB are positively correlated and highly significant. b) Ha received, r=0,322 with a value of p = 0.018, p<0.05 means that organizational commitment and OCB correlated positively and significantly. c) Ha received, r=0,448 with a value of p = 0.001, p<0.05 means that job satisfaction and organizational commitment positively and significantly correlated. d) Ha received, r=0,379 with a value of p = 0.000, p<0.05 means that job satisfaction and organizational commitment and OCB are positively correlated and highly significant.